EMERGENCY SWITCHING AND ANALYSIS OF THE TRANSIENT STATES OF AN INTERLEAVED CONVERTER - Przytuła, Katarzyna (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The growing number of renewable energy sources, active compensators of reactive power and other devices requiring power electronic systems increases the number of higher harmonics in current and power grid voltage waveforms. The paper presents one of the possible solutions of using vector control VOC in parallel converters that can work with the power grid. The study includes simulations of an interleaved converter’s operation during such disturbances as interruption or short circuit. The mutual interaction of converters is also analyzed for currents flowing in the individual phases.